Przysięga władcom Królestwa Polskiego z udziałem duchowieństwa katolickiego - Jemielity, Witold (Prawo Kanoniczne, 2002)
There has been close relationship of the church institutions with the state ones. People prayed in churches on behalf of the current ruler of the country, especially on his birthdays, name days and anniversary of coming to the throne. However, the most significant, according to the law, was the oath taken by all the subjects together with the members of the tsar family. There were two kinds of oaths taken by tha subjects: one taken immediately after the coming to the throne of the tsar and the other, taken just before taking over state offices or for the soldiers who have just joined up the army. There existed detailed regulations as regards who, when and in what way had to fulfill it. The contens of the oath to the specific ruler was quite similar, however, after January Uprising the distinct features of the Congress Kingdom and Tsar Russia started to disappear. In the first half of the century the oath was taken in Polish, while in Augustów Guernica it was also taken in Lithuanian. In the second half of the century the people who spoke Russian took the oath in that language, as far as it concerned civil offices, however in churches it was taken in a local language. It concerned people who have just joined up the army, were appointed to the post mayor, chief of the group of villages, guards of the forests and others. The oaths were taken by the clergymen even if they took place not in the church. Immediately after the November and January Uprisings again the loyalty towards the king and tsar was expressed.